Drug-eluting stents versus bare-metal stents in acute myocardial infarction with cardiogenic shock. Issue 15 (7th February 2017) - Ledwoch, Jakob; Fuernau, Georg; Desch, Steffen; Eitel, Ingo; Jung, Christian; de Waha, Suzanne; Poess, Janine; Schneider, Steffen; Schuler, Gerhard; Werdan, Karl; Zeymer, Uwe; Thiele, Holger
Abstract : Objectives: The aim of the present study was to assess the outcome of patients with acute myocardial infarction (AMI) complicated by cardiogenic shock (CS) receiving drug-eluting stents (DES) compared with bare-metal stents (BMS). Data comparing these two stent technologies in AMI with CS were limited. Methods: A total of 783 patients with AMI and CS undergoing early revascularisation were included in the randomised Intra-aortic Balloon Pump in Cardiogenic Shock II trial (n=600) and the associated registry (n=183). Patients receiving no stent or both, DES and BMS, were excluded. Primary end point was the composite of 1-year mortality or re-AMI. Results: Of the total cohort, 652 (83%) patients received either solely DES or BMS and were included in the present analysis. Of these, 276 (42%) patients received DES and 376 (58%) received BMS. After adjustment for baseline characteristics, there was no significant difference between DES and BMS regarding the primary end point (HR 0.83 (CI 0.64 to 1.06); p=0.14). There was an independent association of BMS use with older age, atrial fibrillation and coronary single-vessel disease. DES use was associated with prior known dyslipidaemia, baseline haemoglobin level, anterior AMI and treatment at frequently enrolling centres. Conclusions: Despite the frequent use of DES nowadays, a substantial number of patients were treated by BMS in AMI complicated by CS. After adjustment for risk factors, the 1-year outcome of patients treated by DES compared with BMS was similar. Trial registrationnumber: www.clinicaltrials.gov : NCT00491036 .